Assessing ITN textile preferences: A comparative study of polyethylene and polyester nets across different settings in Burkina Faso - Hervé Hien; Aristide S. Hien; Fidèle Y. Bacyè; Hermann Badolo; Alfred Tiono; Cheick O. Diallo; Serge M.A. Somda; Hermann Bazié; Matilibou Guira; Nicolas Meda (PLoS ONE, 2025)
Insecticide-treated nets (ITNs) are crucial for preventing malaria and other vector-borne diseases, effectively reducing transmission and mortality rates. However, their uptake remains low, influenced by textile preferences, with polyester nets being favored for comfort, despite their shorter lifespan compared to other materials. A study in Burkina Faso aimed to understand community preferences for ITN fabrics across different environmental contexts to improve malaria control strategies. Using a mixed-methods approach, the study surveyed and interviewed urban and rural communities in three climatic zones of Burkina Faso to identify socio-economic, environmental, and cultural factors shaping ITN material preferences. The study found that 95.2% (95% CI: 94.6–95.7) of participants had a preference for a specific ITN fabric, with 93% (95% CI: 92.3-93.6) favoring polyester over polyethylene, citing superior comfort, breathability, and protection. Regional differences emerged, with rural areas and the Humid savannah-Sahelian zone showing a stronger preference for polyester nets, especially in larger sizes. The study recommended that malaria control programs prioritize polyester-based nets, offer larger sizes for rural populations, use smaller mesh sizes, and adopt rectangular designs to improve coverage and comfort. Urban populations emphasized comfort and efficacy, while rural areas focused more on durability and size. Factors like ease of maintenance, comfort, and local climate were significant in shaping preferences. The study concluded that tailoring ITN distribution strategies to regional needs such as adjusting net size and mesh could improve malaria control efforts. These insights can guide the optimization of malaria prevention programs, enhancing their effectiveness and long-term sustainability in diverse settings.